Hubungan Pengetahuan, Sikap, Dan Perilaku Tentang Perawatan Hipertensi Pada Lansia Yang Menderita Hipertensi di Johar Baru Jakarta Pusat - Cicilia Nony Ayuningsih Bratajaya; Gerardina Sri Rejeki (STIKes Karsa Husada Garut, 2020)
The aging process of elderly will leads to decreased organ function, therefore many health problems could occur, one of them is hypertension which can cause serious illness complications. Knowledge, attitudes, and behavioral treatment of hypertension among elderly with hypertension is necessary to explore. The purpose of this study was to determine the knowledge, attitudes, and behaviors about hypertension treatment among elderly. This quantitative study was used a cross sectional design by involving 58 elderly people who suffering from hypertension in one hamlet at Johar Baru, Central Jakarta. The sampling process was used total sampling. The results showed knowledge (p-Value=0.043) and attitudes (p-Value=0.034) towards the treatment of hypertension have a significant relationship with the behavior of hypertension treatment among elderly with hypertention (pValue <0.05). In conlusion, it is important to increase community’s knowledge and the awareness of hypertention behaviour treatment through the health promotion program at posyandu for the elderly. Keywords: knowledge, attitude, behavior, hypertension treatment, elderly